2013
DOI: 10.1111/tan.12238
|View full text |Cite
|
Sign up to set email alerts
|

HLA alleles and HLA‐B27 haplotypes associated with susceptibility and severity of ankylosing spondylitis in a Portuguese population

Abstract: Human leukocyte antigen (HLA)-B27 is the mostly known major histocompatibility complex (MHC) gene associated with ankylosing spondylitis (AS). Nonetheless, there is substantial evidence that other MHC genes appear to be associated with the disease, although it has not yet been established whether these associations are driven by direct associations or by linkage disequilibrium (LD) mechanisms. We aimed to investigate the contributions of HLA class I and II alleles and B27-haplotypes for AS in a case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…The highly polymorphic amino acid chains of DQB1 are capable of forming the peptide binding groove that presents antigen to CD4 + T-helper cells [27], and controlling the immune response [28, 29]. Previous studies reported that HLA-DQB1 was associated with radiographic severity in AS [30, 31]. The different alleles of HLA-DQB1 were also associated with the age of AS onset [31].…”
Section: Discussionmentioning
confidence: 99%
“…The highly polymorphic amino acid chains of DQB1 are capable of forming the peptide binding groove that presents antigen to CD4 + T-helper cells [27], and controlling the immune response [28, 29]. Previous studies reported that HLA-DQB1 was associated with radiographic severity in AS [30, 31]. The different alleles of HLA-DQB1 were also associated with the age of AS onset [31].…”
Section: Discussionmentioning
confidence: 99%
“…These conformational changes are caused by the binding of variety of peptides to alleles of MHC II. In addition, the associations of MHC II alleles with various diseases have been previously reported [17], [18], [19].…”
Section: Introductionmentioning
confidence: 92%
“…The mechanisms leading to AS are unknown, although human leukocyte antigen B27 (HLA-B27) is known a major risk factor for AS [5]. HLA-B27 is known a genetic marker present in 90%–95% of AS patients [6].…”
Section: Introductionmentioning
confidence: 99%